Objectives of University Industry Collaboration in Nepal: Observation of Students, Professors and Industrial Leaders - Pokharel, Dhruba Raj; Pathak, Ganesh Prasad (Saptagandaki Journal, 2023)
The collaborative relationship between university and industry is becoming crucial research phenomena for professors, students, industrial leaders, government and the general public in the advanced developing as well as underdeveloped economies. It has become more imperative to the management schools and institutes and research centers. In the prevailing knowledge economy universities are called to produce innovative and creative manpower ready to job in the organizations. This research was conducted in Nepalese business management schools operating under the three leading universities, namely Tribhuvan University, Pokhara University and Kathmandu University. Apart from the students and professors, the perception of business community leaders also has been included in regard to attainability of the objectives of university industry collaboration in Nepal. The objective of the study was to find the perception of students, course facilitators and industrial leaders about the level of attainability of the stated objective of UIC. With some differences all respondentsfound the objectives of UIC are attainable in Nepal. Such kind of research is important to the universities, especially business management educators, the industries and the government to frame education policy and curriculum.